Effect of probiotics supplementation on acute diarrhea in infants: a randomized double blind clinical trial - I Gusti Ngurah Sanjaya Putra; Sudaryat Suraatmaja; I Ketut Nomor Aryasa (Paediatrica Indonesiana, 2007)
Background Probiotics has advantages as a supplement formanagement of infants with acute diarrhea. It influences theduration of diarrhea by enhancing immune responses, elaboratesantimicrobial substances and occupies intestinal mucosal sites,inhibits the attachment and the growth of pathogenic organismsby achieving competitive exclusion and microbial balance.Objective To assess the clinical effects of probiotics supplementationon acute diarrhea in infants.Methods This was a double blind, randomized clinical controlledtrial performed on infants aged 1-12 months old with acutediarrhea, hospitalized in Sanglah Hospital, Denpasar. Subjectswere divided into two groups; the treatment group had standardmanagement with adjuvant probiotics, while the control groupreceived standard management with placebo.Results From 70 infants enrolled in this study, the mean durationof diarrhea in treatment group was significantly shorter than thatin the placebo group, 49.03 hours (SE 3.09) (95%CI 42.98;55.08)vs 73.03 hours (SE 3.28) (95%CI 66.61;79.45); P=0.001.Regarding failure of the treatment, probiotics supplementationhad relative risk reduction (RRR) of 67% and absolute riskreduction (ARR) of 57%. In multivariate cox regression analysisit was found that only probiotics supplementation influenced theduration of acute diarrhea in infants.Conclusion Probiotics can shorten the duration of acute diarrhea,and is safe as an adjuvant to standard management for infantswith acute diarrhea.